1983
DOI: 10.1002/zaac.19834970213
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis der Hydrate des Typs MX2 · 1 H2O mit M = Sr, Ba und X = Cl, Br, I. Kristallstrukturen des Strontiumchlorid‐Monohydrats, SrCl2 · 1 H2O, und des Strontiumbromid‐Monohydrats, SrBr2 · 1 H2O

Abstract: Die Strukturen des SrCl2 · 1 H2O, orthorhombisch, Pnma, a = 1088,1(1), b = 416,2(1), c = 886,4(1) pm, Z = 4, drö = 2,92 Mg m−3, R = 0,052 für 755 Reflexe und des SrBr2 · 1 H2O, orthorhombisch, Pnma, a = 1146,4(1), b = 429,5(1), c = 922,9(1) pm, Z = 4, drö = 3,88 Mg m−3, R = 0,056 für 762 Reflexe wurden nach der Schweratommethode bestimmt und mit Fourier‐ und Least‐squares‐Verfahren verfeinert. Die Struktur besteht aus [SrX2 · H2O]n‐Schichten senkrecht [100] mit SrH2OSrH2O‐Zick‐Zack‐Ketten parallel [010]. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…H20; for symmetry codes see Table 3. (2) Freiburg & Lutz, 1983). This is shown from a decrease of both the.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…H20; for symmetry codes see Table 3. (2) Freiburg & Lutz, 1983). This is shown from a decrease of both the.…”
Section: Discussionmentioning
confidence: 95%
“…The coordination of the water molecules is type B after Chidambaram, Sequeira & Sikka (1964). Additional structure details are given (8) 0-75 -0-1197(1) 2"12 (2) 0"12343(8) 0.75 0'3353(I) 2.12(2) 0.3444 (3) 0.75 0.0997 (4) 2'36 (5) 0.386 (6) 0.75 0.148 (7) 5(3) 0.361 (7) 0.75 0"016 (9) in Vajnstejn & Pinsker (1949, 1950, Dyke & Sass (1964) and Engelen, Freiburg & Lutz (1983). The structures of the iodide monohydrates are more symmetric with respect to the H bonds present than those of the bromides and chlorides as predicted in earlier work (Lutz & Christian, 1982;Engelen, c~;'~ c,i Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several crystallographic studies of anhydrous (Sass, Brackett & Brackett, 1963;Smeggil & Eick, 1971) and monohydrated (Dyke & Sass, 1964;Engelen, Freiburg & Lutz, 1983;Lutz, Buchmeier & Engelen, 1987) strontium bromides have been carried out. Early studies (Herrmann, 1931;Jensen, 1940) showed that the title compound was likely to be isostructural with the analogous chloride.…”
Section: Commentmentioning
confidence: 99%